PENGARUH PERSEPSI ATAS EFEKTIFITAS SISTEM PERPAJAKAN, KEPERCAYAAN, TARIF PAJAK DAN KEMANFAATAN NPWP TERHADAP KEPATUHAN MEMBAYAR PAJAK (STUDI EMPIRIS PADA WAJIB PAJAK UMKM MAKANAN DI KPP PRATAMA PEKANBARU SENAPELAN) - Ainil Huda; Yesi Mutia Basri; Julita - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect perception of effectiveness of taxation system, trust, tax rate and benefit of NPWP Of Tax Payment Compliance (Empirical Study Taxpayer micro small and medium enterprises food in KPP Pratama Pekanbaru Senapelan). This study uses accidental sampling with 86 samples obtained from the calculation formula slovin. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 17 for Windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on the variable tax payment compliance. Partial regression test (t test ) indicates that the variable perception of effectiveness of taxation system, trust and benefit of NPWP effect on tax payment compliance. But, variable tax rate not effect on tax payment compliance. The magnitude of the effect caused by Adjusted R2 by four variables together against the dependent variable 52,9%, while the remaining 47,1% is effect by other variables not examined in this study.Keywords: Effectiveness, Trust, Rate, Benefit and Compliance.